2002
DOI: 10.1002/1521-4095(20020816)14:16<1137::aid-adma1137>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Micrometer-Scale Spherical Assemblies of Polymer Particles

Abstract: sponse analyzer (EG&G, Model 1025). The complex impedance plots of the samples were recorded in the frequency range from 1 to 10 5 Hz. The cationic transference numbers, t+, were determined by the steady-state current technique proposed by Bruce and Vincent [28]. The details are given by Reiche et al [29]. Ni was used as a working electrode (A= 0.5 cm 2 ) and Li as counter and reference electrode for cyclic voltammetry.Solid-State NMR: One-dimensional 7 Li static, 27 Al magic-angle spinning, and 1 H/ 29 Si cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 1 publication
1
75
0
Order By: Relevance
“…Velev et al [28,29,30] were the first to report a method for the preparation of colloidosomes by templating octanolin-water emulsions stabilized by latex particles and subsequently removing the octanol core by dissolution in ethanol. Structures of similar architecture have been obtained by templating water-in-oil emulsions [31,32]. Multilayer shells consisting of alternating positive and negative polyelectrolytes and/or nanoparticles have also been prepared by using layer-by-layer assembly techniques, with the final hollow shells being obtained by removal of the central, sacrificial colloidal particles [33,34].…”
Section: Colloidosomesmentioning
confidence: 99%
“…Velev et al [28,29,30] were the first to report a method for the preparation of colloidosomes by templating octanolin-water emulsions stabilized by latex particles and subsequently removing the octanol core by dissolution in ethanol. Structures of similar architecture have been obtained by templating water-in-oil emulsions [31,32]. Multilayer shells consisting of alternating positive and negative polyelectrolytes and/or nanoparticles have also been prepared by using layer-by-layer assembly techniques, with the final hollow shells being obtained by removal of the central, sacrificial colloidal particles [33,34].…”
Section: Colloidosomesmentioning
confidence: 99%
“…As early as 2002, Pine et al [233][234][235] reported the assembly of nanoscale spherical polymer beads into monodisperse (∼5 µm) supraballs (Fig. 22) using a co-flow PDMS chip and a tubing/pipette tip device.…”
Section: Examples Of Microfluidic Particle Productionmentioning
confidence: 99%
“…When the emulsion droplets of the colloidal suspension are evaporated, the colloidal particles form close-packed crystals in a spherical shape [82][83][84]. In contrast, when particles with a repulsive interparticle potential are confi ned in the droplet, the particles form non-close-packed crystals without evaporation [85].…”
Section: Biological Toolsmentioning
confidence: 99%